ADB-API-Tracker e ADB-Tracker: uma Solução em Software e Hardware para Orientação de Operações Agrícolas em Zonas de Manejo - Schemberger, Elder Elisandro (2019)
The growth of agribusiness has been an effect of the investments made in order to increase efficiency in production and reduce its costs. These investments include computer systems and embedded electronic devices used in the management of agricultural production, both by farmers and the scientific community. This technological evolution leads to faster and more accurate decision making, especially in the context of Precision Agriculture and Digital Agriculture, which can be made available to small producers by dividing productive agricultural areas into management zones (ZMs), making their implementation cheaper. To define ZMs empirical or grouping methods are employed, usually assisted by software. However, the software and hardware used in this segment are usually proprietary and dependent on specific technologies, which may prevent their use by small producers. The ADB-Tracker platform, which provides the interpretation of the shapefiles of the ZMs generated by the ADB-Map application of the AgDataBox platform (ADB), or even generated by another one, is made possible in order to enable the navigation process in ZMs during agricultural operations. Precision Agriculture software in order to guide the farmer in the field during an agricultural operation. This navigation was performed by the software ADB-Tracker and performed by a smartphone or even using its own hardware, designed with free hardware components, thus providing total mastery over it, easy maintenance, scalability, low cost, and portability. The operations data is persisted locally as well as in the ADB-API-Tracker, which implements routines and generates reports regarding the agricultural operations performed in the ZMs with ADB-Tracker application support. This work also presents the validation process of this solution in the perspective of user acceptance test (UAT), which aimed to highlight strengths and weaknesses of ADB-Tracker, resulting in a qualitative report on improvements and deficiencies for the application software, guiding the key requirements to be addressed for improvement and implementation.